Directional ellipticity on special domains: Weak Maximum and Phragmén–Lindelöf principles. (July 2019) - Capuzzo Dolcetta, Italo; Vitolo, Antonio
Abstract: We prove the validity of maximum principles for a class of fully nonlinear operators on unbounded subdomains Ω ⊂ R n of cylindrical type. The main structural assumption is the uniform ellipticity of the operator along the bounded directions of Ω, with possible degeneracy along the unbounded directions.